ANALISIS MASLAHAH TERHADAP PENOLAKAN AKAD PERNIKAHAN PASANGAN LGBT DALAM KONSTRUKSI HUKUM KELUARGA ISLAM - Sugitanata, Arif; Adnan, Idul; Hamroni, Hamroni; Hardiyatullah, Hardiyatullah (STIS Darussalam Bermi, 2023)
This research highlights the view of Islamic family law on the rejection of the marriage contract of LGBT couples as a marriage, which is seen through the lens of Maslahah theory. Through a literature study using qualitative research based on the scalpel of Maslahah theory, The research underlines that marriage in Islam is not only an agreement between two individuals but also an institution governed by certain conditions and pillars, including the existence of male and female parties who are permitted according to Sharia, as well as the existence of a guardian, dowry, and fair witnesses. In the context of LGBT couples, the marriage contract does not fulfil these conditions, so it cannot be considered a marriage contract in Islamic family law. In addition, the rejection is analysed through Maslahah theory, which emphasises the importance of maintaining the integrity of the family structure, moral values and spiritual goals in society. The refusal is interpreted as an attempt to preserve the general welfare by maintaining social harmony and adherence to Islamic principles. It shows that the rejection of marriage contracts for LGBT couples is not discriminatory but rather the result of a deep understanding of the concept of marriage in Islam, with the aim of achieving broader welfare and protecting the institution of the family as the basic social and spiritual unit. This research confirms that Islamic law is a dynamic and adaptive system seeking to promote justice and welfare in accordance with religious principles and the needs of society. Thus, the rejection of marriage contracts for LGBT couples in Islamic family law can be understood as part of an effort to maintain the harmony of society without abandoning the underlying religious principles.